Aumento da recuperação metalúrgica de nióbio na etapa de aluminotermia - Vinícius Elias de Godoy (2023)
One of the main key performance indicators used in mining plants is the metallurgical recovery, which is calculated in percentage terms as the amount of the metal of interest contained in the feed that reached the product after a given process. In mining, the higher this indicator, the higher the performance of a process and consequently of an entire business. This work is based on a technical and statistical study aimed at optimization the recovery of niobium from the aluminothermic stage of CMOC Brasil, the second largest ferroniobium producer in the world. The study presents how the aluminum excess indicator was created, and its importance within aluminothermy in the search for recovery maximization and product quality assurance in relation to contaminating elements. As excess aluminum is modified, recoveries of niobium, silicon and other contaminating elements also vary. From this, it is possible to maximize the aluminum excess and niobium recovery when the contaminant contents in the fed pyrochlore concentrate are in accordance with the specification or to reduce the aluminum excess and consequent niobium recovery to produce alloy from out of specification concentrate. At the end of this study, an annual production gain of more than 300 tons of niobium and a reduction in aluminum consumption of more than 500 tons per year are presented, thus resulting in a financial profit for the company of 225 million reais in just over 3 years.